An Analysis of Student Necessities English for Computer and Network Engineering at SMK Negeri 1 Takalar - Imma, Nur Anisma; Rahmat, Subhan (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
The process of learning English with ESP (English for Specific Purposes) in the world of education often runs less than optimally. One of the contributing factors is the lack of lesson planning so that learning takes place irrelevant to the field of knowledge they teach. For this reason, it is necessary to have a learning plan which will begin by analyzing students' needs for learning English with special objectives. Therefore the research aims to find and describe students' needs for ESP English focusing on the Necessities of what language aspects the learners need. This needs to be done so that the English language learning materials with special purposes (ESP) received by students are in accordance with the field of knowledge they are capable of and the field of work they will be engaged in. This research is based on a quantitative descriptive approach. The object of this research was class XI students of Computer and Network Engineering, SMK Negeri 1 Takalar. The data collection technique used was a questionnaire, a questionnaire. Then the data obtained will be classified so that the needs of Computer and Network Technology (TKJ) students for learning English can be identified, then they will be described. The results of this study will be used as a reference for subsequent research, namely syllabus planning and development of teaching materials for ESP English.